Analisis Pengaruh Sektor Perdagangan Terhadap PDRB Sumatera Utara Dengan Menggunakan Metode Location Quotient - Hutagalung, Anastasia; Sianturi, Andrew (Pusat Pengembangan Kompetensi Aparatur Perdagangan, 2022)
Regional economic growth is one of development indicator which is closely related to the level of people's welfare. One of the components used to measure economic growth is the Gross Regional Domestic Product (GRDP). In GRDP, it can be seen which of the economic sector that contributes the most. The purpose of this study is to analyze the specialization of the economic sector, especially trade sector, to be developed in North Sumatra Province. The data used in this study is secondary data in form of data on the Gross Regional Domestic Product (GRDP) of North Sumatra Province in 2016-2021 which is processed using the Location Quotient (LQ) approach. The result showed that the Agriculture, Forestry, and Fisheries sectors; Real Estate; and Trade are sectors that have more influence than other regions nationally, so these three sectors need to be the government's attention. The trade sector which is the sector with number 3 specialization in North Sumatra compared to other regions nationally is an interesting thing to be highlighted because it is the sector with the largest tax revenue in North Sumatra and the GRDP of the sector always grow except in 2020 due to the Covid-19 Pandemic.